Occupational stress, bullying and resilience in old age. - Zsoldos, E; Mahmood, A; Ebmeier, K (2014)
Our working years increasingly extend into the late 60s and may soon include the 70s for some people. Thus the question whether work stress has a cumulative effect in older age, and whether older employees are more vulnerable to certain sources of work stress, such as bullying in the work place, is becoming increasingly relevant. We review some of the mechanisms, which translate cumulative stress at work into ill health, particularly in older age, and summarise what is known about the effect of age-specific stress, taking age-related bullying as an example.